Efektivitas E-Arbitration Sebagai Solusi Penyelesaian Sengketa Bisnis Di Era Ekonomi Digital - Zainal Parhan (AL-Ikhtiar : Jurnal Studi Islam, 2026)
The growth of the digital economy and cross-border business transactions necessitates a rapid, efficient, and flexible dispute resolution mechanism. Conventional arbitration, which still requires the physical presence of the parties and manual document filing, is considered incompatible with the fully digital dynamics of contemporary business. This study aims to analyze the juridical foundation for implementing E-Arbitration (electronic arbitration) in Indonesia, assess its effectiveness as a business dispute resolution instrument, and identify the practical challenges encountered. This study employs a normative juridical method, utilizing statutory and conceptual approaches. The primary legal materials, namely Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution and the Law on Electronic Information and Transactions (ITE Law), are analyzed alongside secondary legal materials, including scientific journals and official publications from arbitration institutions. The results indicate that the practice of E-Arbitration possesses a robust legal basis through the synchronization of the freedom of contract principle in the Arbitration Law with the recognition of electronic documents and signatures in the ITE Law. The implementation of E-Arbitration within national arbitration institutions has proven capable of reducing transportation costs and accelerating case resolution times. Nevertheless, this practice still faces obstacles concerning cybersecurity, limited digital infrastructure, and the compliance of the losing party in executing the arbitral award. This study recommends strengthening the technical regulations regarding electronic procedural law within the national arbitration legal framework. Abstrak Pertumbuhan ekonomi digital dan transaksi bisnis lintas batas menuntut tersedianya mekanisme penyelesaian sengketa yang cepat, efisien, dan fleksibel. Arbitrase konvensional yang masih mensyaratkan kehadiran fisik para pihak dan pemberkasan dokumen secara manual dinilai kurang sejalan dengan dinamika bisnis kontemporer yang serba digital. Penelitian ini bertujuan untuk menganalisis landasan yuridis penerapan E-Arbitration (arbitrase elektronik) di Indonesia, mengkaji tingkat efektivitasnya sebagai instrumen penyelesaian sengketa bisnis, serta mengidentifikasi tantangan yang dihadapi dalam praktiknya. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan (statute approach) dan pendekatan konseptual (conceptual approach). Bahan hukum primer berupa Undang-Undang Nomor 30 Tahun 1999 tentang Arbitrase dan Alternatif Penyelesaian Sengketa serta Undang-Undang Informasi dan Transaksi Elektronik dianalisis bersama bahan hukum sekunder berupa jurnal ilmiah dan publikasi resmi lembaga arbitrase. Hasil penelitian menunjukkan bahwa praktik E-Arbitration memiliki dasar keabsahan hukum yang cukup kuat melalui sinkronisasi asas kebebasan berkontrak dalam UU Arbitrase dengan pengakuan dokumen dan tanda tangan elektronik dalam UU ITE. Pelaksanaan E-Arbitration di lembaga arbitrase nasional terbukti mampu memangkas biaya transportasi dan mempersingkat waktu penyelesaian perkara. Meskipun demikian, praktik ini masih menghadapi kendala terkait keamanan siber, keterbatasan infrastruktur digital, serta kepatuhan pihak yang kalah dalam melaksanakan putusan. Penelitian ini merekomendasikan penguatan regulasi teknis mengenai hukum acara persidangan elektronik dalam kerangka hukum arbitrase nasional.